2010
DOI: 10.2754/avb201079020319
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Diagnostic Features in Three Dogs Naturally Infected with Borrelia spp.

Abstract: The aim of this study was to present clinical and neurological signs, laboratory abnormalities, serologic and/or molecular findings in three dogs from the region of Brno in the Czech Republic. All dogs were naturally infected with Borrelia burgdorferi sensu lato. The evidence of borrelial infection was proved by serial blood sampling for IgM and IgG anti-borrelial antibodies or plasma PCR. The dogs manifested corresponding clinical signs and one or more of the following criteria were fulfilled: (1) 4-fold or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Clinical syndromes together with PCR and serial serology indicate a very likely borrelia induced disease. In all three of our dog case studies (Schánilec et al 2010), the immune response and PCR findings indicated an early disseminated stage of a borrelial infection.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Clinical syndromes together with PCR and serial serology indicate a very likely borrelia induced disease. In all three of our dog case studies (Schánilec et al 2010), the immune response and PCR findings indicated an early disseminated stage of a borrelial infection.…”
Section: Discussionmentioning
confidence: 60%
“…We also describe three cases of dogs naturally infected with borreliosis (Schánilec et al 2010). All presented cases showed clinical and diagnostic features that strongly indicated borrelial infection.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies claim that cardiac manifestations of borreliosis are uncommon in dogs (Nielsen et al, 2002). However, recent information (Schanilec et al, 2010) shows that the incidence of cardiac manifestations could be higher than expected. Studies in experimental animals (mainly rodents) showed that 100% of those infected with Borrelia sp.…”
Section: Discussionmentioning
confidence: 86%
“…It includes varying degrees of atrioventricular (AV) block. We have seen a positive dog with a 1 st degree AV block and prolonged QT interval that also suffered from neurological signs and had high levels of borrelial antibodies, which suggest that the pathogen was involved in the arrhythmia (Schanilec et al, 2010). In humans, complete AV block has been reported in as much as 80% of cases (Levy and Durray, 1988;Gasser et al, 1999;Bateman and Sigal, 2000;Lo et al, 2003;Nalmas et al, 2007).…”
Section: Discussionmentioning
confidence: 88%